2022
DOI: 10.3389/fnmol.2022.840948
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes and Microglia Exhibit Cell-Specific Ca2+ Signaling Dynamics in the Murine Spinal Cord

Abstract: The spinal cord is the main pathway connecting brain and peripheral nervous system. Its functionality relies on the orchestrated activity of both neurons and glial cells. To date, most advancement in understanding the spinal cord inner mechanisms has been made either by in vivo exposure of its dorsal surface through laminectomy or by acute ex vivo slice preparation, likely affecting spinal cord physiology in virtue of the necessary extensive manipulation of the spinal cord tissue. This is especially true of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 105 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…While IL-6, PGE2, and cyclooxygenase 2 (COX2) release increased in astrocytes, completely different pro-inflammatory profile was observed in microglia with increased release of IL-1β, TNF-α, nitric oxide (NO), iNOS and STAT3 activation (Lu et al, 2014). Even though both cell types express integrins and TLR4, time of their activation and downstream signalling pathways may differ, since it has been shown that astrocytes and microglia have cellspecific Ca 2+ signalling dynamics (Rieder et al, 2022). Astrocytes and microglia express multiple P2Y and P2X receptors but those receptors are differentially activated by nucleotides in a context specific manner upon pathophysiological conditions and further mediate different long-term changes of these cells during inflammatory gliosis (Abbracchio and Ceruti, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…While IL-6, PGE2, and cyclooxygenase 2 (COX2) release increased in astrocytes, completely different pro-inflammatory profile was observed in microglia with increased release of IL-1β, TNF-α, nitric oxide (NO), iNOS and STAT3 activation (Lu et al, 2014). Even though both cell types express integrins and TLR4, time of their activation and downstream signalling pathways may differ, since it has been shown that astrocytes and microglia have cellspecific Ca 2+ signalling dynamics (Rieder et al, 2022). Astrocytes and microglia express multiple P2Y and P2X receptors but those receptors are differentially activated by nucleotides in a context specific manner upon pathophysiological conditions and further mediate different long-term changes of these cells during inflammatory gliosis (Abbracchio and Ceruti, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical astrocytic Ca 2+ activity was recorded upon drug application. Analysis of Ca 2+ imaging data was performed using the custom-made detection and analysis software MATLAB (MSparkles v. 1.8.18)(Stopper et al, 2023) as previously described (Rieder et al, 2022). Shortly, fluorescence fluctuations at basal Ca 2+ concentrations (F 0 ) were computed along the temporal axes of each individual pixel using a polynomial fitting in a least-squares sense.…”
Section: Methodsmentioning
confidence: 99%
“…For acute brain slices of 11-to 13-week-old GLAC ct2/wt xA1AR wt/wt xGCaMP3 fl/fl mice and GLAC ct2/wt xA1AR fl/fl xGCaMP3 fl/fl mice were prepared as described above. 1.8.18) (Stopper et al, 2023) as previously described (Rieder et al, 2022). Shortly, fluorescence fluctuations at basal Ca 2+ concentrations (F0) were computed along the temporal axes of each individual pixel using a polynomial fitting in a least-squares sense.…”
Section: Ca 2+ Imaging In Hippocampal Slicesmentioning
confidence: 99%
“…Ca 2+ event analysis was performed using a custom-made analysis software developed in MATLAB [ 93 ] as previously described [ 94 ]. The algorithm detects fluorescence fluctuations with respect to basal per-pixel fluorescence levels (F0), computed by fitting a polynomial curve along the temporal axis of each pixel.…”
Section: Methodsmentioning
confidence: 99%